Systematics and evolution of the orb-weaving spider genus Wagneriana F.O. Pickard-Cambridge, 1904 (Araneae; Araneidae) - Garcia, Jimmy Jair Cabra (2018)
Although several Neotropical genera of the family Araneidae were revised using modern taxonomic standards, species-level phylogenies and phylogenetic relationships among genera remains poorly understood. This study was designed to test the monophyly of the Neotropical araneid genus Wagneriana, F. O. Pickard-Cambridge, 1904 and its phylogenetic placement by conducting a total evidence analysis. The combined matrix included 167 phenotypic characters and approximately 4,800 base pairs generated for three mitochondrial and six nuclear loci. The dataset consists of 82 terminals representing 100% of the described diversity of the genus Wagneriana, (37 species after taxonomic changes) plus five undescribed species and 33 outgroup terminals of 31 species. To evaluate the phylogenetic significance of the phenotypic evidence, comparisons between total evidence analyses and molecular-only analyses were conducted. In addition, to evaluate the effect of the alignment and optimality criteria, multiple analytical approaches were conducted using the programs POY, TNT, RAxML, GARLI, IQtree and MrBayes. In general, the results obtained across the different approaches showed congruence. In all the cases, W. carimagua Levi, 1991 and W. uropygialis, Levi, 1991 were nested within the genera Parawixia F. O. Pickard-Cambridge, 1904 and Alpaida O. Pickard-Cambridge, 1889, respectively, and the remaining nominal species of the genus Wagneriana fell into three main clades, neither of which formed a pair of sister taxa. However, sister-group relationships of the main clades, as well as, its internal relationships were strongly influenced by the employed analytical approach. The election of alignment criteria had comparable topological effects to that of optimality criteria. Within the maximum likelihood context, the program choice affected the maximization of the likelihood score and the tree topology. Although phenotypic evidence comprised only 2.80-3.05% of the total evidence matrices, it had impact in support values and topology. In general, the inclusion of phenotypic evidence, irrespective of the optimality criterion used, increased the support values of several ingroup and outgroup clades. Furthermore, the monophyly of several clades was only recovered with the addition of phenotypic characters. In accordance with the phylogenetic results, a new araneid genus is proposed and Paraverrucosa Mello-Leitão, 1939 is resurrected. Moreover, five Wagneriana species are newly described and complementary descriptions for seven species are provided. This study presents the first total evidence phylogenetic analysis of a Neotropical Araneidae genus and discusses the impact of the inclusion of phenotypic evidence and the choice of alignment and optimality criteria in phylogenetic analyses